GRAPEVINE VEIN-CLEARING VIRUS IS MEALYBUG-BORNE BUT NOT MEALYBUG-TRANSMITTED - Luaay K. Khalaf,; Yu Zhang,; Mustafa Adhab, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This article investigates the ability of two types of mealybugs, citrus (Planococcus citri) and longtailed (Pseudococcus longispinus) mealybugs, of acquiring and transmitting Grapevine vein-clearing virus (GVCV) in a greenhouse setting. Mealybugs are the primary vectors for most Badnaviruses, and only a few species have been shown to be aphid-transmitted. In this study, we tested the acquisition and transmission ability of two mealybug species using GVCV-infected and healthy grapevines in a greenhouse setting for three consecutive seasons. This study determined that acquisition time by the mealybugs could be as low as three days, yet the transmission of GVCV from infected grapevines to healthy grapevines by these two mealybug species was unsuccessful. Additionally, with the use of previously-developed species-specific primers, this study determined that those mealybugs captured in the greenhouse facilities at the University of Missouri could not be identified using these primers, and required primers that were specific to their regional diversity. This study contributes to the wider understanding of the acquisition and transmission of GVCV by certain mealybug species.